Teaching and Learning of English Language Programme in Public Primary Schools in Nigeria: Problems and Ways Forward - Audu Atete Catherine; Ominike Faith (Researchparks Publishing, 2021)
English language is one of the core subject offered from the basic education to higher education in Nigeria. The programme is important to the success of students in schools and out of school lives. It is unfortunate that English language programme is plagued with many problems. This article discussed the problems faced by teaching and learning of English language programme in primary schools in Nigeria. Secondary data were used to support the points raised in the article. The secondary data were sourced from print material and online publication by recognized institutions and authors. Inadequate funding of English programmes, insufficient professional English language teachers, inadequate instructional resources, inadequate infrastructural facilities, poor capacity development programmes for English language teachers are problems of teaching and learning of English language programmes in Nigerian public primary schools. In order to solve these problems, the paper suggested: adequate funding of English programmes at primary schools, provision of adequate instructional resources, provision of adequate infrastructural facilities and constant training and retraining of teachers of English language in English language programmes.